2013
DOI: 10.1002/adem.201300236
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Magnesium Porous Structures by Infiltration Casting for Biomedical Applications

Abstract: Magnesium and its alloys are currently considered to be a promising metallic biomaterial. The interest in magnesium alloys arises from their biocompatibility, bioabsorbility, and especially from their mechanical properties, which are more compatible to those of human bone than the mechanical properties of other metallic biomaterials, such as stainless steel and titanium. A medical application in which magnesium is gaining interest is regenerative medicine where scaffolds are used to create tissues from cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Chloride ions in plasma will also react with Mg(OH) 2 to form MgCl 2 [ 9 ]; here, the model can be extended to consider two reactive species for Mg(OH) 2 , and assume, for simplicity, that the outer layer consists of an isotropic mixture of MgCO 3 and MgCl 2 . In practice, the magnesium block will be pitted and have holes that will presumably affect its corrosive properties as well [ 42 ]; this is currently being explored by the authors. There is thus plenty of scope to improve the current model, in order to describe more realistically the corrosion properties of magnesium based orthopaedic implants in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Chloride ions in plasma will also react with Mg(OH) 2 to form MgCl 2 [ 9 ]; here, the model can be extended to consider two reactive species for Mg(OH) 2 , and assume, for simplicity, that the outer layer consists of an isotropic mixture of MgCO 3 and MgCl 2 . In practice, the magnesium block will be pitted and have holes that will presumably affect its corrosive properties as well [ 42 ]; this is currently being explored by the authors. There is thus plenty of scope to improve the current model, in order to describe more realistically the corrosion properties of magnesium based orthopaedic implants in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…44 In general, the Young's modulus and maximum stress of porous Mg under compression increases with reduction of porosity and pore size. From the tabulated data (Table 1), the authors concluded that the compressive Wen et al [43][44][45] Pure Mg PM (Carbamide) 30-35 Yamada et al 46 AZ91 Infiltration casting -Zhuang et al 47 Pure Mg PM (Carbamide) 7, 38, 55 Fang et al 48 Pure Mg Laser perforation technique 42.6-51 Witte et al 49,50 AZ91D PM (Salt) 72-76 Gu et al 51 Pure Mg GASAR a 28 AE 1.3 Nguyen et al 52 Pure Mg Infiltration casting 35-80 Kirkland et al 53 Pure Mg Infiltration casting -Zhang et al 54 Pure Mg PM (Salt) -Seyedraoufi and Mirdamadi 55 Mg-Zn PM (Carbamide) 21, 29, 36 Kang et al 56 HA-coated Mg Spark plasma sintering (SPS) 50, 60, 70 Capek and Vojtech 57,58 Pure Mg PM (Carbonate hydrogen ammonium) 29-31 Trinidad et al 59 ZM20, ZMW200, ZXM200, AZ91E, and WE43…”
Section: Manufacturing Processes and Mechanical Propertiesmentioning
confidence: 99%
“…Porous magnesium and its alloy have been recently recognized as a promising biomaterial for bone substitution due to their outstanding biocompatibility, degradability, and low elastic modulus . It has been found that porous magnesium with proper pore size and porosity has closer elastic modulus and strength to those of natural bone, avoiding the uneven stress at the bone‐implant interface, and achieving the desired combination with natural bone . However, the extensive application of porous magnesium is limited due to its overpaid corrosion rate, high degradation and vast formation of hydrogen before the adequate healing of damaged tissues.…”
Section: Introductionmentioning
confidence: 99%